Shared decision making for patients needing dentofacial orthopedics, orthognathic surgery, and conventional non-surgical fixed appliance therapy: a comparison between Pakistani patients' and clinicians' perspective - Fatima Naz NAJAM; Waqar JEELANI; Maheen AHMED; Mirza Ezaaf SHUJA (Dental Press Editora, 2024)
ABSTRACT Introduction: Shared decision making (SDM) involves presenting patients with relevant information about a health issue and reaching a clinical decision based on their preferences. However, its application in orthodontics lacks documentation. Objective: This study aimed to assess and compare the perspectives of patients and clinicians on SDM in different cases. Methods: A cross-sectional study was conducted at a tertiary care hospital in Pakistan, involving 90 patients categorized into three groups (dentofacial orthopedics, orthognathic surgery, and conventional non-surgical fixed appliance treatment). Following clinical assessment and treatment plan discussions, patients and clinicians completed a 12-item dyadic observing patient involvement in decision making (OPTION) questionnaire, to gauge their perspectives on SDM. Mean OPTION scale scores were compared using paired sample t-tests between clinicians and patients, and intergroup comparisons utilized paired sample t-tests and Pearson correlation coefficients. Results: OPTION scores were similar between patients/parents and clinicians. However, statistically significant differences were found regarding the questions about "different sources of information", "different options (including the possibility of doing nothing)" and "concerns regarding management", with the patients giving overall lower OPTION scores. Patients gave lower SDM OPTION scores for conventional orthodontic treatment, but higher scores for orthopedic and orthognathic surgery, as compared to the clinicians. Conclusions: The current study revealed an overall consensus in the mean total scores of OPTION scales between patients and clinicians. However, when stratified, patients showed higher SDM scores for orthopedic and orthognathic cases, and lower scores for conventional orthodontic treatment.